PENGENDALIAN BIAYA DAN WAKTU DENGAN METODE EARNED VALUE PROYEK FAMILIA URBAN BEKASI - Tri Rahmanto; Syapril Janizar (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2022)
Project management is the process of planning, coordinating organization, and controlling resources so that objectives are achieved effectively and efficiently. This study aims to determine the performance of the project in terms of cost and time conditions with the earned value method on the Bekasi Urban Familia Housing Development Project. The method in this study uses quantitative methods, quantitative research is research on data that is numerical and tends to use analysis. The method used is by field observations, interviews with implementing contractors, and data processing from the field such as working drawings and basic unit prices. Based on the results of the study, the actual cost of the 18th week was Rp. 2,859,922,545.75, while the planned budget for that week was Rp. 3,381,087,652.62. Project performance in the form of actual progress weights issued until that week was 58.04% while in that week it was planned to be 67.98%. Estimated cost and time projections at the end of the project are obtained that the cost to complete the remaining work during that time (BETC) is IDR 897,934,488.98 and the total cost the final amount (EAC) was Rp. 4,927,465,511.02. The time to complete the project (SETC) is 151 days with a total planning time of 147 days. Due to the delay in project completion, the contractor will be fined Rp. 23,301,600 the total final cost of the project according to the work contract is Rp. Rp 4,950,767,111.02.